Szasz-Mirakjan type operators providing a better error estimation - Duman, Oktay; Oezarslan, M. Ali (Pergamon-Elsevier Science Ltd, 2007)
In this work, giving a modification of the well-known Szasz-Mirakjan operators, we prove that the error estimation of our operators is better than that of the classical Szasz-Mirakjan operators. Furthermore, we obtain a Voronovskaya type theorem for these modified operators. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Szasz-Mirakjan operators; the Korovkin type approximation theorem; modulus of continuity; the Voronovskaya type theorem